Hubungan Fenetik Pisang (Musa Spp) berdasarkan Karakter Morfologi di Wilayah Provinsi Gorontalo - Elsi Gogou; Novri Youla Kandowangko; Febriyanti; Jusna Ahmad; Aisyah Ahmad (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
Banana (Musa spp) is a tropical fruit plant that has many benefits and important roles for the community. This study aims to provide information on the morphological characteristics of bananas in the Gorontalo Province and their phenetic relationships. This study uses a descriptive method to describe the diversity of morphological characters of bananas (Musa spp) with data collection using a survey study method (exploration) which is carried out by tracing or exploring the location of the Gorontalo Province, purposive sampling (Purposive Stratified Sampling) by seeing and observing directly the morphological characters of bananas (Musa spp). Data analysis using the Unweighted Pair Group with Mean of Arithmetic (UPGMA) method with the Gower Genelar Similarity Coeffiicient formula in the MVSP (Multi-Variate Statistical Package) v.3.1 computer program. The results of the study showed that there were 4 types of bananas found in the Gorontalo Province which showed unique morphological variations, namely Kepok Bananas have the characteristic of quite large leaf morphology, Abati Bananas have a unique yellowish color, Green Butota Bananas have morphological characteristics with very thick fruit and Wild Bananas have characteristics with a large number of stones. Based on the results of the clustering, 2 main groups were formed which separated at a cosiness of 0.643 (64.3%) found between Abati Bananas, Green Butota, and Wild Bananas, while Kepok Bananas showed a very distant relationship with a cosiness value of 0.482 (48.2%). The results of this study have the potential to support the preservation of local varieties and support the sustainable genetics management through the identification of varieties that are tolerant to salinity and drought.